2006
DOI: 10.1111/j.1600-0501.2006.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion contact formation by fibroblasts cultured on surface‐modified dental implants: an in vitro study

Abstract: A major consideration in designing dental implants is to create a surface that provides strong attachment of the implant to bone, connective tissue and epithelium. The aim of the present study was to examine the influence of different treatments of titanium (Ti) implant surfaces on focal adhesion contact (FAC) formation in fibroblast cultures. Human gingival fibroblasts were cultured on glass sheets and polished Ti discs with different surface coatings (applied by physical vapor deposition (PVD): Ti, titanium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 38 publications
(41 reference statements)
9
94
1
1
Order By: Relevance
“…The increase in surface roughness could be because of the sharp edges of alumina particle on the surface, in addition to the action of the blasting process on the titanium. 7 Ra values were however lower than those found by 16 Größner-Schreibere et al, 15 and this could be because they used a larger particle size (125 µm).…”
Section: Blasting With Aluminacontrasting
confidence: 51%
“…The increase in surface roughness could be because of the sharp edges of alumina particle on the surface, in addition to the action of the blasting process on the titanium. 7 Ra values were however lower than those found by 16 Größner-Schreibere et al, 15 and this could be because they used a larger particle size (125 µm).…”
Section: Blasting With Aluminacontrasting
confidence: 51%
“…This finding links to other work which shows that increases in surface roughness can have a negative impact on fibroblast cell adhesion and may potentially prevent initial adaption of the cells to surface [21]. This effect is possibly linked to the number of focal adhesion contacts being formed between the cell and the surface as Grossner-Schreiber et al had previously shown that there were an increased number of focal adhesion contacts on surfaces with a lower Ra value [14]. However, this is not seen for the unprocessed polymer, which shows a lower level of adhesion and also shows much lower surface analysis values.…”
Section: Discussionsupporting
confidence: 59%
“…An in vitro study with mouse fibroblasts had revealed that MTT activities and total protein contents were significantly increased on TiN coated polished Ti surfaces compared to the thermally oxidized and laser radiation structured surfaces [47]. In another study, glass sheets coated with Ti and TiN presented the highest number of focal adhesion contacts (FACs) of human gingival fibroblasts as a proof of good adhesion [48]. Clem et al [49] applied TiN coating onto Ti alloys by Microwave Plasma Chemical Vapor Deposition and investigated the biocompatibility of these newly formed TiN surfaces using different cell lines.…”
Section: Discussionmentioning
confidence: 99%